2004
DOI: 10.5565/rev/elcvia.67
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Weights in a Multiple Classifier Handwritten Word Recognition System Using a Genetic Algorithm

Abstract: Automatic handwritten text recognition by computer has a number of interesting applications. However, due to a great variety of individual writing styles, the problem is very difficult and far from being solved. Recently, a number of classifier creation methods, known as ensemble methods, have been proposed in the field of machine learning. They have shown improved recognition performance over single classifiers. For the combination of these classifiers many methods have been proposed in the literature. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…A genetic algorithm is used to actually determine an optimal combination of weight values. Comparing performance based weighting and genetic algorithms, it was found that the highest recognition rate was obtained with genetic weight optimisation [22].…”
Section: Weighted Voting Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…A genetic algorithm is used to actually determine an optimal combination of weight values. Comparing performance based weighting and genetic algorithms, it was found that the highest recognition rate was obtained with genetic weight optimisation [22].…”
Section: Weighted Voting Mechanismsmentioning
confidence: 99%
“…A number of other modification methods have been investigated including modifications to feature selection [14,22,25], sampling methods [19,21,24], node splitting [15,20], performance evaluation [20], considering similarity between training examples [20,23,26] and others, details of which can be found in [15].…”
Section: Other Random Forest Modificationsmentioning
confidence: 99%
“…Another improvement of RF is accomplished by replacing majority voting with weighted voting. Since not all trees are equally responsible for incorrect classification of individual instances it is useful to use weights in the votes of the trees (RF with weighted voting) [22]- [27]. A description of all weighted voting schemes that were used is given in Section III.…”
Section: G Classificationmentioning
confidence: 99%
“…Finally genetic algorithms (fifth weighted voting scheme) were used for the calculation of weights [27]. The weights of the chromosome with the highest fitness value, encountered during all generations, are the final result and are used for the weighted voting.…”
Section: H(a) H(a| B) Su 20 H( A) H( B)mentioning
confidence: 99%
“…The second algorithm [20], the third [21] and the fifth algorithm [22] are based on the metrics between databases. The fourth [23] and the sixth [24] the use the weighting of trees according to their classification rate. The authors performed a number of experiments on the Al'zhamer databases to study the evolution of random forest performances when implementing the weighted vote or the classical majority vote.…”
Section: B the Voting Mechanismmentioning
confidence: 99%